Oligodendrocyte pathology exceeds axonal pathology in white matter in human amyotrophic lateral sclerosis. Issue 3 (8th June 2020) - Lorente Pons, Alejandro; Higginbottom, Adrian; Cooper‐Knock, Johnathan; Alrafiah, Aziza; Alofi, Ebtisam; Kirby, Janine; Shaw, Pamela J; Wood, Jonathan D; Highley, J Robin
Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease. The majority of cases are sporadic (sALS), while the most common inherited form is due to C9orf72 mutation (C9ALS). A high burden of inclusion pathology is seen in glia (including oligodendrocytes) in ALS, especially in C9ALS. Myelin basic protein ( MBP ) messenger RNA (mRNA) must be transported to oligodendrocyte processes for myelination, a possible vulnerability for normal function. TDP43 is found in pathological inclusions in ALS and is a component of mRNA transport granules. Thus, TDP43 aggregation could lead to MBP loss. Additionally, the hexanucleotide expansion of mutant C9ALS binds hnRNPA2/B1, a protein essential for mRNA transport, causing potential further impairment of hnRNPA2/B1 function, and thus myelination. Using immunohistochemistry for p62 and TDP43 in human post‐mortem tissue, we found a high burden of glial inclusions in the prefrontal cortex, precentral gyrus, and spinal cord in ALS, which was greater in C9ALS than in sALS cases. Double staining demonstrated that the majority of these inclusions were in oligodendrocytes. Using immunoblotting, we demonstrated reduced MBP protein levels relative to PLP (a myelin component that relies on protein not mRNA transport) and neurofilament protein (an axonal marker) in the spinal cord. This MBP loss was disproportionate to the level of PLP and axonal loss, suggesting that impaired mRNA transport may be partly responsible. Finally, we show that in C9ALS cases, the level of oligodendroglial inclusions correlates inversely with levels of hnRNPA2/B1 and the number of oligodendrocyte precursor cells. We conclude that there is considerable oligodendrocyte pathology in ALS, which at least partially reflects impairment of mRNA transport. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.